2021
DOI: 10.1186/s12934-021-01585-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of the precursor supply pathway for the overproduction of the nC14-surfactin isoform with promising MEOR applications

Abstract: Background Surfactin, a representative biosurfactant of lipopeptide mainly produced by Bacillus subtilis, consists of a cyclic heptapeptide linked to a β-hydroxy fatty acid chain. The functional activity of surfactin is closely related to the length and isomerism of the fatty acid chain. Results In this study, the fatty acid precursor supply pathway in Bacillus subtilis 168 for surfactin production was strengthened through two steps. Firstly, pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The proportion of the C 16 isoform was also increased, which contributed to the whole yield of surfactin from strain TPS8. Many studies have also demonstrated that the proportion of surfactin isoforms can be altered by genetically modifying the fatty acid biosynthesis pathway 26,30 . Hu et al 30 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportion of the C 16 isoform was also increased, which contributed to the whole yield of surfactin from strain TPS8. Many studies have also demonstrated that the proportion of surfactin isoforms can be altered by genetically modifying the fatty acid biosynthesis pathway 26,30 . Hu et al 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have also demonstrated that the proportion of surfactin isoforms can be altered by genetically modifying the fatty acid biosynthesis pathway. 26,30 Hu et al 30 reported a 6.4-fold increase in the proportion of nC14 surfactin after the elimination of pathways competing for the precursors and overexpression of BTE and exhibited higher surface activity and better performance in oil washing. In this study, surfactin may exhibit different properties due to the increased proportion of the C 16 isoform.…”
Section: Changes In the Composition Of Surfactin In B Subtilis Tp1mentioning
confidence: 99%
See 2 more Smart Citations
“…By way of comparison, we note, for example, that the MI27-derived BioS is more effective than surfactin isoforms produced by Bacillus subtilis isolate LSFM-05 (de Faria et al 2011), those produced by B. subtilis SL having a CMC value of 154 mg/L and a ST of 28.68 mN/m (Wu et al 2022) and surfactin isoforms produced by Bacillus nealsonii S2MT (Phulpoto et al 2020). In means of the ST reduction power, it is more efficient than surfactin isoforms produced by B. subtilis BS-37 displaying a CMC value of mg/L (Liu et al 2014), Bacillus amyloliquefaciens MO13-derived surfactin isoforms displaying a CMC value of 36 mg/L and an ST of 27 mN/m (Moro et al 2022), engineered surfactin isoforms produced by B. subtilis 168 having a CMC value of 38-36 mg/L with potential ST of 28 mN/m (Hu et al 2021) and surfactin isoforms derived from B. subtilis #309 having a CMC value of 15 mg/L with potential ST of 28 mN/m (Janek et al 2021).…”
Section: St Measurement and Determination Of The Cmc Valuementioning
confidence: 99%